The Feasibility of Archipelago Children Literature Teaching Materials on Text-Based of Class V SDN 067091 Medan Kota Sub-district, Indonesia - Dahlia Dahlia; Wisman Hadi; M. Oky Ferdian G (BIRCU, 2019)
This study aims to know the feasibility of archipelago children literature teaching materials on text-based of class V SDN 067091 Medan Kota sub-district, Indonesia. The type of this study is research and development which is the development of archipelago children literature teaching materials on text-based that deserve to support literature learning in elementary school. The product of archipelago children literature teaching materials is developed to support literary learning in elementary schools have met the requirements and are feasible to use based on the validation of material experts and design. The response to archipelago children literature teaching materials on text-based in literary material is very good and in accordance with the needs of students. It concludes that the use of archipelago children literature teaching materials on text-based is more effective in improving student learning outcomes. This was revealed from the student learning outcomes after being taught with developed teaching materials, namely an increase in learning outcomes from the average 78.98 with a good category to 86.11 with a very good category.